Anticytomegalovirus antibody titres are not associated with caregiving burden in younger caregivers. (23rd April 2014) - Vitlic, Ana; Phillips, Anna C.; Gallagher, Stephen; Oliver, Chris; Lord, Janet M.; Moss, Paul
<x xml:space="preserve">Abstract</x> Objective This analysis examines whether or not younger caregivers, parents of children with developmental disabilities, differed from controls in terms of cytomegalovirus (CMV) seropositivity and CMV‐specific antibody titre. Secondly, it examined whether any particular socio‐demographics, health behaviours, or psychological/caregiving variables were associated with a higher CMV antibody titre among caregivers. Design Young caregivers and age‐ and sex‐matched controls were compared with respect to their reported health behaviour and psychosocial status as well as latent virus control. Methods One hundred and seventeen parents of children with developmental disabilities and 52 control parents completed standard measures of health behaviours, socio‐demographics, perceived stress, depression and anxiety, caregiver burden, child problem behaviours. They also provided a blood sample assayed for the presence of CMV‐specific antibody. Results Caregivers were no more likely to be CMV positive than controls and did not have higher antibody titres against CMV. In addition, there was no association between CMV antibody titre in seropositive caregivers and any of the psychological/caregiving variables. However, higher CMV antibody titres were significantly associated with a higher BMI, lower exercise levels, smoking, and lower fruit and vegetable and fat intake among seropositive caregivers. Conclusions These data suggest that in the absence of immunosenescence, the chronic stress of caregiving is not sufficient to compromise the immune response to persistent CMV infection. However, an indirect mechanism to poorer health in caregivers might be via adoption of disadvantageous health behaviours in response to stress. <boxed-text content-type="box" id="bjhp12092-blkfxd-0001" position="anchor" orientation="portrait"> Statement of contribution What is already known on this subject? Older caregivers of spouses with dementia show a poorer immune response against latent viruses when compared to age‐ and sex‐matched controls. Younger parental caregivers of children with developmental disabilities show a poorer antibody response to vaccination. What does this study add? The study showed no association between caregiving stress and CMV antibody titre in young caregivers. There were higher CMV antibody titres in the caregivers who engage in unhealthy behaviours. </boxed-text>